Engineering tools and solutions for sustainable transportation planning - Knoflacher, Hermann; Ocalir-Akunal, Ebru, 1972- (Engineering Science Reference, 2017)
"This book explores the underlying causes of traffic flow problems: transport and urban structures are optimized not as a system for the benefits of the society in a sustainable way but optimized for individual optimization for car users. This book delves into the need for creating sustainable environments, while designing transport structures, and considers system behavior"--